2019
DOI: 10.37236/7589
|View full text |Cite
|
Sign up to set email alerts
|

Classification of the Hyperovals in PG(2,64)

Abstract: In this paper, we present a full classification of the hyperovals in the finite projective plane $\mathrm{PG}(2,64)$, showing that there are exactly 4 isomorphism classes. The techniques developed to obtain this result can be applied more generally to classify point sets with $0$ or $2$ points on every line, in a broad range of highly symmetric incidence structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Our aim in this section is to classify all flocks of the quadratic cone in PG (3,64), by bringing to bear our knowledge of ovals of PG(2, 64), based on Vandendriessche's determination of the hyperovals of PG(2, 64) [57]. It is clear that the most convenient model to approach this classification from this perspective is that of herds of ovals of PG (2,64).…”
Section: Computational Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our aim in this section is to classify all flocks of the quadratic cone in PG (3,64), by bringing to bear our knowledge of ovals of PG(2, 64), based on Vandendriessche's determination of the hyperovals of PG(2, 64) [57]. It is clear that the most convenient model to approach this classification from this perspective is that of herds of ovals of PG (2,64).…”
Section: Computational Resultsmentioning
confidence: 99%
“…Proof. In [57] it was shown that, up to equivalence, there are exactly four hyperovals in PG(2, 64): the regular hyperoval, the Adelaide hyperoval, the Subiaco I hyperoval, the Subiaco II hyperoval. The corresponding o-polynomials can be read off from the q-clans above: t 1/2 gives the regular hyperoval, f 0 from the Adelaide q-clan C A gives the Adelaide hyperoval, f 0 from the Subiaco q-clan C S gives the Subiaco I hyperoval and f a from herd H(C S ) arising from the Subiaco q-clan gives the Subiaco II hyperoval, where a 2 + a + 1 = 0.…”
Section: Computational Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hyperoval with a group of order 12 was generalised to the infinite family of Adelaide hyperovals in [9] in 2003. In 2019 [40], hyperovals of PG(2, 64) were classified by Vandendriessche.…”
Section: Hyperovals In Pg(2 64)mentioning
confidence: 99%
“…In particular, certain geometrical objects in finite projective planes known as hyperovals (see [BCP06] and the references therein for the list of known infinite families of hyperovals), give rise to such Vandermonde sets. There are further examples of Vandermonde sets known for small fields (see for example [AH19, Example 7]), but a full classification is out of reach (simply because a full classification of hyperovals appears to be out of reach [Va19]). We ask the following question related to the enumeration of Vandermonde sets.…”
Section: Vandermonde Setsmentioning
confidence: 99%